Modelling Algorithms and Protocols for Congestion Control in TCP/IP Networks - Martyshkin, A. I. (2024 International Conference on Industrial Engineering, Applications and Manufacturing (ICIEAM), 2024)
The article is devoted to the study of algorithms and protocols for congestion control in Transmission Control Protocol/Internet Protocol networks. In modern data transmission networks, the Transmission Control Protocol is of key importance, providing reliable communication between devices. Among its components a special place is occupied by the algorithm of congestion control, which determines the efficiency of data transmission. This paper considers the problem of congestion control, which is one of the fundamental and complex problems in the study of computer networks. The main objective of the study is to evaluate the effectiveness of congestion control methods using the developed mathematical model. The object of the study is congestion in Transmission Control Protocol networks, and the subject is congestion control protocols. Computer modelling techniques are used to conduct the study. The study shows the significant impact of congestion control protocols on network performance as well as different approaches to congestion control depending on network characteristics. The results obtained include comparative analysis of protocols, selection of modelling techniques and tools, development of simulation model, simulation experiments and evaluation of congestion control protocols. Evaluating the effectiveness of congestion control protocols using a mathematical model allows us to anticipate and analyze network behavior in different scenarios and optimize protocol parameters to achieve the best performance and stability of data transmission. In conclusion, we draw conclusions on the work.